2018
DOI: 10.1016/j.jcol.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The use of local anesthesia and sedation in transanal hemorrhoidal dearterialization with Doppler

Abstract: The treatment of hemorrhoidal disease has never been as innovated as in recent decades. The transanal hemorrhoidal dearterialization with Doppler (THD) was described under general anesthesia or spinal blockage and there is no use of local anesthesia reports. This study aims to evaluate the safety of the use of local anesthesia with sedation in THD. For this purpose, two cases are reported describing the technical and safety analysis and results. Both patients were women with grade II and III hemorrhoidal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Anorectal surgery requires adequate anesthesia due to its multiple nerve supply [ 9 ]. Painful stimuli can be blocked either with regional or general anesthesia (GA), usually with muscle relaxants [ 8 ]. Different studies have suggested that switching from GA or regional anesthesia like saddle block and or spinal anesthesia to local infiltration or perianal block (PAB) may prove advantageous for proctologic surgeries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorectal surgery requires adequate anesthesia due to its multiple nerve supply [ 9 ]. Painful stimuli can be blocked either with regional or general anesthesia (GA), usually with muscle relaxants [ 8 ]. Different studies have suggested that switching from GA or regional anesthesia like saddle block and or spinal anesthesia to local infiltration or perianal block (PAB) may prove advantageous for proctologic surgeries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Controversial results have been published before as to the occurrence of pain following open hemorrhoidectomy under local anesthesia versus spinal anesthesia or general anesthesia. In the United Kingdom and in Brazil, studies found a similar mean pain scores in 10 days follow-up [ 8 , 13 ] yet in India and in Egypt, the mean rate of pain was seen to be lower post open hemorrhoidectomy under local anesthesia (LA) compared to that done under SA [ 1 , 2 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthesia (LA) is adequate for the majority of anal surgical procedures [ 8 ]. LA produces sensory and motor blockade in the peri-anal region with an effect on peripheral nerve endings and therefore produces varying and unpredictable degrees of anal canal relaxation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthesia (LA) is adequate for the majority of anal surgical procedures [ 8 ]. LA produces sensory and motor blockade in the peri-anal region with an effect on peripheral nerve endings and therefore produces varying and unpredictable degrees of anal canal relaxation [ 8 ]. Operative time has been shown to be different according to the anesthetic technique used in terms of time saved during operation according to studies done by Kushwaha and Baghel with their colleagues comparing the use of LA versus spine and GA for open hemorrhoidectomy [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation